Manajemen Fungsi Hubungan Masyarakat Dalam Meningkatkan Jumlah Mahasiswa Baru Di Institut Agama Islam Syarifuddin Lumajang - Rokhmad Rokhmad; Abdul Muis; Zainal Abidin (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
Public relations is one of the management functions that has a dominant role in the successful management of educational organizations, especially private Islamic Religious Universities which carry out the tasks of education, research and community service as stated in the Tri Dharma of Higher Education. The focus of the discussion in the research is on the management of implementing the public relations function within the Syarifuddin Islamic Institute, Lumajang with schools/madrasahs, government and private agencies, as well as alumni in increasing the number of new students. This research uses a descriptive qualitative approach with a case study type of research at the Syarifuddin Lumajang Islamic Institute. Data sources using observation techniques, in-depth interviews and documentation. Meanwhile, data analysis is done by induction and interpretation in research. The aim of this research is to describe the function of public relations from the planning, organizing, implementation to evaluation of the public relations function implemented by the Syarifuddin Lumajang Islamic Institute with schools/madrasahs, government and private agencies and alumni in increasing the number of new students. The results of this research show that the implementation of the function of community relations with schools/madrasahs, government and private agencies as well as relations with alumni has had an impact on increasing the number of new students at the Syarifuddin Lumajang Islamic Institute. Keywords: public relations function management, increase in the number of new students. Hubungan masyarakat merupakan salah satu fungsi manajemen yang memiliki peran dominan pada keberhasilan pengelolaan organisasi pedidikan, khususnya Perguruan Tinggi Keagamaan Islam Swasta yang mengemban tugas pendidikan, penelitian dan pengabdian kepada masyarakat sebagaimana tertuang dalam Tri Dharma Perguruan Tinggi. Fokus pembahasan dalam penelitian pada manajemen penerapan fungsi hubungan masyarakat di lingkungan Institut Agama Islam Syarifuddin, Lumajang dengan sekolah/madrasah, instansi pemerintah dan swasta, serta alumni dalam meningkatkan jumlah mahasiswa baru. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus di Institut Agama Islam Syarifuddin Lumajang. Sumber Data yang menggunakan teknik observasi, wawancara mendalam, dan dokumentasi. Sementara analisa datanya dengan induksi, dan interpretasi di dalam penelitian. Adapun tujuan penelitian ini untuk mendeskripsikan fungsi hubungan masyarakat baik dari proses perencanaan, pengorganisasian, pelaksanaan hingga evaluasi dari fungsi hubungan masyarakat diterapkan oleh Institut Agama Islam Syarifuddin Lumajang dengan sekolah/madrasah, instansi pemerintah dan swasta dan alumni dalam meningkatkan jumlah mahasiswa baru. Hasil penelitian ini menunjukkan penerapan fungsi hubungan masyarakat dengan sekolah/madrasah, instansi pemerintah dan swasta serta hubungan dengan alumni berdampak pada peningkatan jumlah mahasiswa baru di Institut Agama Islam Syarifuddin Lumajang. Kata Kunci: manajemen fungsi hubungan masyarakat, meningkatan jumlah mahasiswa baru.